Expert Consensus on Digital Leadership Competencies for School Principals in Malaysia: A Fuzzy Delphi Approach - Hamzah, Nur Hafiza; Omar, Intan Marfarrina; Mohd Radzi, Norfariza (Management Research Journal, 2024)
In today's rapidly evolving digital era, school principals must possess strong digital leadership competencies to effectively manage and lead educational institutions. Digital transformation in education requires more than just technological infrastructure; it demands leaders who can integrate digital tools strategically while fostering an innovative learning environment. Keeping this in mind, the goal of this study is to identify the essential digital leadership competencies for school principals in Malaysia. Using the Fuzzy Delphi Method (FDM), this study aims to obtain expert consensus on the key dimensions and elements of digital leadership. A total of 15 experts, including Senior Lecturers from Institut Aminuddin Baki (IAB), Senior Officers from PPD, JPN, and KPM, as well as experienced school principals, participated in this study. An instrument containing four competency dimensions: Personal Competencies, Job Requirement Competencies, Organizational Environmental Competencies, and Social Role Competencies was presented for expert evaluation. The findings indicate that all proposed elements were accepted, with the fuzzy scores meeting the FDM threshold (d≤0.2), achieving expert agreement above 75% (87% to 100%), and passing the alpha cut value (α-cut ≥0.5) with scores ranging from 0.918 to 0.960. The defuzzification process ranked competencies based on expert consensus, identifying Personal Competencies as the most critical dimension. Among the key elements, technological mastery, risk-taking, resilience, and exemplary technology use were found to be the most crucial for school principals. Additionally, competencies related to digital data management, ethical digital practices, and stakeholder collaboration were highly prioritized. In conclusion, this study successfully validates a framework for digital leadership competencies in the educational sector. The findings provide valuable insights for policymakers in designing professional development programs and leadership training. Schools can utilize these results to enhance principal training, ensuring they are equipped to lead in a technology-driven educational landscape. Future research should explore the implementation of these competencies in various educational settings to further refine digital leadership strategies.